2022
DOI: 10.1186/s12864-022-08331-z
|View full text |Cite
|
Sign up to set email alerts
|

Time-course RNA-seq analysis reveals stage-specific and melatonin-triggered gene expression patterns during the hair follicle growth cycle in Capra hircus

Abstract: Background Cashmere goat is famous for its high-quality fibers. The growth of cashmere in secondary hair follicles exhibits a seasonal pattern arising from circannual changes in the natural photoperiod. Although several studies have compared and analyzed the differences in gene expression between different hair follicle growth stages, the selection of samples in these studies relies on research experience or morphological evidence. Distinguishing hair follicle growth cycle according to gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…But analgen is maintained by important factors such as IGF-1, HGF, VEGF, and the morphogenesis of the hair follicle depends on the Wnt, Shh, Notch, BMP, and other signaling pathways interplay between the epithelial and mesenchymal cells [ 11 ]. Recent studies have identified the Wnt, TGF- beta, and Hippo signaling pathways to promote hair follicle growth [ 12 ], and p-cadherin to maintain anagen by regulating the canonical Wnt signaling and suppressing TGF-β2 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…But analgen is maintained by important factors such as IGF-1, HGF, VEGF, and the morphogenesis of the hair follicle depends on the Wnt, Shh, Notch, BMP, and other signaling pathways interplay between the epithelial and mesenchymal cells [ 11 ]. Recent studies have identified the Wnt, TGF- beta, and Hippo signaling pathways to promote hair follicle growth [ 12 ], and p-cadherin to maintain anagen by regulating the canonical Wnt signaling and suppressing TGF-β2 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Cashmere goats, though measured expression of HOXC13 was higher in telogen, expression was determined in both phases and even higher expression determined in low eece yielding Cashmere goats [19]. However another studies [18,31] found that HOXC13 expression was higher in anagen, compared to catagen and telogen. In the presented study, in contradiction to previous ndings, HOXC13 gene expression was measured only anagen phase.…”
Section: Discussionmentioning
confidence: 90%
“…Also, in HF stem cells TGFB and BMP activation cause proliferating keratinocytes to transiently withdraw from the cell cycle thus changing HF phase [16,39]. Li et al (2022) [31] reported that BMP-2 was highly expressed during the anagen by analyzing with time-course RNA-seq analysis on skin biopsies of Inner Mongolia cashmere goats. In comparison of anagen and telogen phases for expression of BMP-2 gene, we have determined a strong upregulation in anagen (P-value = 0,0026).…”
Section: Discussionmentioning
confidence: 99%
“…In Cashmere goats, though measured expression of HOXC13 was higher in telogen, expression was determined in both phases and even higher expression determined in low eece yielding Cashmere goats (Wang et al 2014). However another studies (Wang et al 2018;Li et al 2022) found that HOXC13 expression was higher in anagen, compared to catagen and telogen. In the presented study, in contradiction to previous ndings, HOXC13 gene expression was measured only anagen phase.…”
Section: Discussionmentioning
confidence: 95%
“…2014;Guha et al 2004). Li et al (2022) reported that BMP-2 was highly expressed during the anagen by analyzing with time-course RNA-seq analysis on skin biopsies of Inner Mongolia cashmere goats. In comparison of anagen and telogen phases for expression of BMP-2 gene, we have determined a strong upregulation in anagen (P-value = 0.0026).…”
mentioning
confidence: 99%